2014
DOI: 10.1055/s-0034-1387791
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Hyperandrogenism in Lean Reproductive-Age Women Stimulates Proatherogenic Inflammation

Abstract: We determined the effect of hyperandrogenemia as observed in polycystic ovary syndrome (PCOS) on fasting and glucose-stimulated proatherogenic inflammation markers in lean healthy reproductive-age women. Sixteen lean healthy ovulatory reproductive-age women were treated with 130 mg of DHEA or placebo (n=8 each) for 5 days. Interleukin-6 (IL-6) mRNA and IL-6 release from mononuclear cells (MNC), plasma IL-6 and C-reactive protein (CRP), and MNC-derived (matrix metalloproteinase-2) MMP-2 protein were quantified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Which was in line with Dehdashtihaghighat et al, [43] who observed increased CRP in case of PCOS and they reported that this increase could be due to excess production in the liver under the influence of interleukin-6 and TNF-a , but it was independent on BMI or IR and it could be due to hyperandrogenism in those patients, also, as reported by Gonzalez et al, [54] that is in lean reproductive age women, proatherognic and inflammatory markers increased after raising circulating androgens to levels observed in PCOS. However, the definite cause of CRP increase in PCOS is unknown.…”
Section: Discussionsupporting
confidence: 89%
“…Which was in line with Dehdashtihaghighat et al, [43] who observed increased CRP in case of PCOS and they reported that this increase could be due to excess production in the liver under the influence of interleukin-6 and TNF-a , but it was independent on BMI or IR and it could be due to hyperandrogenism in those patients, also, as reported by Gonzalez et al, [54] that is in lean reproductive age women, proatherognic and inflammatory markers increased after raising circulating androgens to levels observed in PCOS. However, the definite cause of CRP increase in PCOS is unknown.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, OS was augmented in the L group, and it was evidenced by the increased level of MDA and the decreased level of antioxidants in ovarian tissues. Lipid peroxidation may result from excess proinflammatory cytokine production, as evidenced by decreased serum TNF‐α in the present study (Gonzalez et al, ) or IR‐induced hyperglycemia (Ullah et al, ).…”
Section: Discussionmentioning
confidence: 47%
“…Excess androgen also can arrest follicular development indirectly via OS and proinflammatory cytokines, which enhance apoptosis in granulosa cells resulting in bad oocyte quality and finally progressive atresia of ovarian follicles (Rezvanfar et al, ). Excess testosterone could increase nuclear factor kappa B (NF‐κB) gene expression and proinflammatory gene expression and stimulate circulating mononuclear cells (Gonzalez et al, ). This was confirmed in the present study by the increased serum TNF‐α in the L group, and this is compatible with the study of Salmabadi, Mohseni Kouchesfahani, Parivar, & Karimzadeh ().…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation in lean women with PCOS could have other pathogenic mechanisms, but most studies of parameters of chronic low-grade inflammation have been conducted in overweight or obese patients with PCOS. A study of healthy, lean women without PCOS treated with dehydroepiandrosterone sulfate (DHEA-S) showed an increase in inflammatory parameters after an increase in androgen levels [35]. Thus, it can be suggested that the cause of chronic low-grade inflammation in lean patients is hyperandrogenemia.…”
Section: Discussionmentioning
confidence: 99%